Quantification of training load distribution in mixed martial arts athletes: A lack of periodisation and load management - Kirk, C.; Langan-Evans, C.; Clark, D. R.; Morton, J. P. (PLOS ONE, 2021)
The aim of this study was to quantify typical training load and periodisation practices of MMA athletes. MMA competitors (n = 14; age = 22.4 ± 4.4 years; body mass = 71.3 ± 7.7 kg; stature = 171 ±9.9 cm) were observed during training for 8 consecutive weeks without intervention. Seven athletes were training for competitive bouts whilst the remaining 7 were not. Daily training duration, intensity (RPE), load (sRPE and segRPE), fatigue (short questionnaire of fatigue) and body region soreness (CR10 scale) were recorded. Using Bayesian analyses (BF10=3), data demonstrate that training duration (weekly mean range = 3.9-5.3 hours), sRPE (weekly mean range = 1,287-1,791 AU), strain (weekly mean range = 1,143-1,819 AU), monotony (weekly mean range = 0.63-0.83 AU), fatigue (weekly mean range = 16-20 AU) and soreness did not change within or between weeks. Between weeks monotony (2.3 ± 0.7 AU) supported little variance in weekly training load. There were no differences in any variable between participants who competed and those who did not with the except of the final week before the bout, where an abrupt step taper occurred leading to no between group differences in fatigue. Training intensity distribution corresponding to high, moderate and low was 20, 33 and 47%, respectively. Striking drills accounted for the largest portion of weekly training time (20-32%), with MMA sparring the least (2-7%). Only striking sparring and wrestling sparring displayed statistical weekly differences in duration or load. Athletes reported MMA sparring and wrestling sparring as high intensity (RPE=7), BJJ sparring, striking sparring and wrestling drills as moderate intensity (RPE 5-6), and striking drills and BJJ drills as low intensity (RPE=4). We conclude that periodisation of training load was largely absent in this cohort of MMA athletes, as is the case within and between weekly microcycles.